7-6s=-5-6s

Simple and best practice solution for 7-6s=-5-6s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-6s=-5-6s equation:



7-6s=-5-6s
We move all terms to the left:
7-6s-(-5-6s)=0
We add all the numbers together, and all the variables
-6s-(-6s-5)+7=0
We get rid of parentheses
-6s+6s+5+7=0
We add all the numbers together, and all the variables
12!=0
There is no solution for this equation

See similar equations:

| 3k+6=4k | | 12z=10z+20-12 | | 12x-7x=2x+5 | | 7=7+1/10t | | -6x+6(2x+-3)=-5-7x | | 0.2/b=20 | | -4m+3m=3/2 | | x^2+(x–4)^2=20^2 | | 3y^2-11y+12=0 | | 9(2e+1)-3(e-2)=45 | | (x+-8)^4=16 | | -5j=4j-9j | | x^2+13+24=0 | | -q+10=5q-8 | | 9×(x-2)=3x×(x-2) | | 3n-1=3n | | 9(x-1)=90 | | x+√4x+1=5 | | 7(3x-1)/4=-14 | | 2z-4=2z+3 | | 4(2u+8)=5(u+4) | | 7(3x-1)=-14 | | -4c=6c-10 | | −13(23x+5)=−43(12x−8) | | (2/5)+(2/x)=1 | | 9a-8-6=-27 | | -3(1+5x)+1=-107 | | 5+3q=3q | | -5-5(3-4a)=-160 | | 10-3c=8-2c | | 7+x-8=10 | | 76+68+x÷3=80 |

Equations solver categories